Road crash in China from 2003 to 2005 - 周继红 邱俊 赵新才 刘国栋 肖凯 张良 蒋志全 王正国 (Chinese journal of traumatology, 2008)
Objective： To analyze characteristics and causes of road crash and injuries in China from 2003 to 2005. Methods： The data of road crash in 2003-2005 were collected to study the characteristics including total vehicle number, occurrence rates of traffic accidents and serious traffic accidents so as to discuss the causes and characteristics of road crash in China. Results： From 2003 to 2005, the numbers of traffic accidents, injuries and deaths as well as the mortality rates per 100 000 persons and per 10 000 vehicles declined in China. Until 2005, the total number of traffic accidents decreased to 450 000 and deaths to 99 000, with the mortality rate per 10 000 vehicles being 7.6 persons. While the drivers and passengers accounted for 33.2 % and 26.6 % of death casualties respectively in 2005. Most traffic accidents were caused by drivers, especially those with driving experience less than 3 years. Traffic accidents occurred on suburban roads accounted for 60%. The mortality rate of the traffic accidents per 100 km on the first grade road ranked the highest. The mortality rate of the traffic accidents on expressways ranked the highest, with continual increase of death and injury. Conclusions. At present, the increase trend of traffic accidents and casualties in China has been slowed down to some extent and shows a declining tendency, but the situation is far away from being optimistic. In order to cut down the number of traffic accidents and casualties, we should pay more attention to training and managing drivers with less than three driving years and those driving buses. Strict prevention measures should be laid on traffic accidents on first grade roads, expressways and suburban roads as well as the enhancement on improving first-aid system.